1993
DOI: 10.1210/er.14.6.710
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and growth factors in milk

Abstract: Research dealing with hormones/growth factors in milk has progressed rapidly during the last 10 yr from their identification in milk to their regulation of various functions in the maternal organism and in the neonate. Many hormones, growth factors, and bioactive substances present in the maternal organism are present in colostrum and milk, often exceeding concentrations that occur in maternal plasma. Some appear in milk in different, sometimes multiple, forms from that found in maternal serum, reflecting to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 0 publications
2
34
0
4
Order By: Relevance
“…As discussed above, during nursing pups are exposed to several cues from the mother, among which milk is perhaps one of the most important. Although there are no reports of milk composition in rabbits, in the rat, maternal milk contains, besides nutrients, hormones, steroids, antibodies, enzymes, and growth factors, among many other biologically active compounds (Withworth & Grosvenor, 1978;Grosvenor et al, 1993;Rowe & Kennaway, 2002). In contrast to rats, rabbit pups remain alone in the nest for most of the time, and the lack of one or more factors in the milk (or from the mother, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, during nursing pups are exposed to several cues from the mother, among which milk is perhaps one of the most important. Although there are no reports of milk composition in rabbits, in the rat, maternal milk contains, besides nutrients, hormones, steroids, antibodies, enzymes, and growth factors, among many other biologically active compounds (Withworth & Grosvenor, 1978;Grosvenor et al, 1993;Rowe & Kennaway, 2002). In contrast to rats, rabbit pups remain alone in the nest for most of the time, and the lack of one or more factors in the milk (or from the mother, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies have shown that human milk contains a variety of hormones and growth factors [15,16,17,18,19,20,21, 24, 26, 27]. In particular, insulin-like growth factors (IGF) and the epidermal growth factor (EGF) were found in physiological concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Term milk samples (TMS) were collected by manual pressure of the breast, preterm milk samples (PTMS) by using an electrical pump. To standardize the collection, milk samples were taken between 11.00 and 13.00 h, and between 16.00and 20.00 h. To eliminate fat and cell debris, the milk was centrifuged at 2,500 g for 10 min [15]. The milk serum was immediately frozen and stored at –80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides providing nutrients essential to suckling infants, milk contains a large number of bioactive substances, likely to be involved in development (for review, see Grosvenor et al 1993). Early milk, that is, in the early stages of lactation (also known as colostrum) differs substantially from mature milk in contents, including immunoglobulins and other active biological molecules such as growth factors (McGhee et al 1975;Read et al 1984;Baumrucker et al 1993;Purup et al 2007).…”
Section: Introductionmentioning
confidence: 99%